Effects of Anthocyanin-Rich Popping Maize Flour on the Phenolic Profile and the Antioxidant Capacity of Mix-Bread and Its Physical and Sensory Properties - Simić Marijana; Žilić Slađana; Šimuruna Olivera; Filipčev Bojana; Škrobot Dubravka; Vančetović Jelena (Polish Journal of Food and Nutrition Sciences, 2018)
In this study, the effect of anthocyanin-rich popping maize flour on phenolic profile, antioxidant capacity and color of bread were investigated. Texture and sensory properties of maize mix-breads were evaluated also. Replacing 30% of wheat flour with blue- and dark-red-seeded maize flours increased the content of total phenolic compounds, ferulic and p-coumaric acids of mix-breads compared to the control bread. In addition, anthocyanins from maize flours improved functional profile of breads. Despite thermal degradation, the content of anthocyanins in crumb of blue and dark-red maize mix-breads was high and amounted to 142.3 mg CGE/kg and 84.4 mg CGE/kg, respectively. In his acylated and non-acylated forms, cyanidin 3-gluco-side was the most prevalent anthocyanins in maize mix-breads. However, given to the synergistic and antagonistic interaction that arises from the co- existence of numerous antioxidant compounds in food, anthocyanin-rich maize flour had no effect on the increase in the bread antioxidant capacity.